The Effects of One-to-One Laptop Program on Help-Seeking and Homework Completion - Jérémie Bisaillon; Stéphane Villeneuve; Alain Stockless (The Canadian Network for Innovation in Education (CNIE), 2020)
Many students prefer to abandon rather than seek help during their homework. However, seeking support is recognized as an effective learning strategy to complete assignments. Technology-supported classroom could have a beneficial impact on this strategy and, therefore, on homework completion. This article aims to compare students from a one-to-one laptop program to others studying in a traditional classroom environment on their 1) help-seeking strategies and 2) homework completion frequency. Quantitative analyses tend to confirm the initial hypothesis. However, they reveal the necessity to sensitize students regarding the appropriate use of technological tools to ensure their beneficial impact on learning.